Full- field Electroretinogram (ffERG) on color vision deficiency/ Saiful Azlan Rosli and Hamizah Ismail - Rosli, Saiful Azlan; Ismail, Hamizah (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
This study aimed to describe the electrophysiological respond of amplitude and latency time using full-field ERG (FfERG) among colour vision deficiency. Twelve eyes of colour vision deficiency subject were recruited in this study which the mean age of the subjects was 22.0 ± 1.41 years. Psychophysics colour vision test was done by using Nagel Anomaloscope. Room illumination was photopic adapted for 10 minutes, then single flashes of 3 cd.s.m-2 presented until four similar artefacts-free ERG waveforms, which based on ISCEV 2015 protocol. All the data were analysed using a one-sample t-test, which was compared to the normative test value. Cone a-wave amplitude (V) was statistically significant higher by 31.65, 95% CI [21.74, 41.55], p=0.00 than a normal cone a-wave amplitude of -30.73 V. Meanwhile, cone a-wave latency time (ms) shows statistically significant higher by 0.92, 95% CI [0.05, 1.79], p=0.04 than a normal cone a wave latency time of 14.30 ms. Also, cone b-wave amplitude (V) shows a significant lower by -107. 95% CI [-136.94, -77.63], p=0.00 than a normal cone b-wave amplitude of 119.26 V. FfERG techniques ability to detect any abnormality that occurred in the retina and visual pathway related to vision.